Socio‐economic differences in patient participation behaviours in doctor–patient interactions—A systematic mapping review of the literature. (9th August 2019) - Allen, Sarah; Rogers, Simon N.; Harris, Rebecca V.
Abstract: Background: The degree to which patients participate in their care can have a positive impact on health outcomes. This review aimed to map the current literature on patient participation behaviours in interactions with physicians and the extent to which differences in these behaviours can be explained by socio‐economic status (SES). Search strategy: Four electronic databases were searched from 1980 onwards using key words related to socio‐economic status and patient participation behaviours. Study selection: Titles, abstracts and full texts were screened by two reviewers, with the second reviewer screening 20% of all entries. Data extraction: Data on year of publication, country, patient population, setting, patient participation behaviour studied, and SES measure used were extracted. Main results: Forty‐nine studies were included in the review. Most studies were conducted in the United States, and the most commonly studied patient participation behaviour was involvement in decision making. Most studies measured SES using education as an indicator, with very few studies using occupation as a measure. Many studies did not report on participants' medical condition or study setting. Patient participation in their health‐care appointment increased with increasing SES in 24 studies, although in 27 studies no significant association was found. Discussion and conclusions: Current literature was found to be mainly US‐centric. Many studies did not specify participants' medical condition or in what setting the study was undertaken. More studies are needed on less commonly studied patient participation behaviours. It would be helpful for further studies to also include a wider range of SES indicators.